Penggunaan Urea sebagai Sumber Nitrogen pada Proses Biodegradasi Substrat Lumpur Sawit oleh Jamur Phanerochaete chrysosporium - Noferdiman, Noferdiman; Rizal, Yose; Mirzah, Mirzah; Heryandi, Yan; Marlida, Yetti (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The research was conducted to study the biodegradation capability on palm oil sludge substrate by Phanerochaete  chrysosporium   with increasing urea  as  nitrogen  source. The  experiment was  designed using Completely Randomized Design (CRD) with 5 treatments and 4 replications, namely : U-0 = 0,0 %  Urea,    U-1=      0,5  %  Urea,    U-2  =  1,0  %  Urea,    U-3  =  1,5  %  Urea  and  U-4  =  2,0  %  Urea. The observed variables were the amount of spore, C/N ratio, pH, crude fiber, crude protein, lignin, cellulose and enzyme activities. The result of this study showed that added urea were significantly (P<0.01) crude fiber, crude protein, lignin, cellulose and enzyme activities. The use of urea on the first level amounting to  1.5  %  in palm  oil  sludge  can  help  Phanerochaete  chrysosporium   to  reduce  crude  fiber to (30,71%),  lignin (29.89  %),  cellulose (36.42  %) and it  can  increase  the  content  of crude  protein    to    (34.50  %), reduction sugar and enzyme activities.